Cooperative-Based Learning and the Zone of Proximal Development. (April 2015) - Clapper, Timothy C.
Purpose . The purpose of this article is to introducecooperative-based learning and Vygotsky'szone of proximal development (ZPD) to the simulation literature as two important mutually supportive learning theories that may enhance the effectiveness ofsimulation-based instruction . Design/Methodology/Approach . A brief literature review ofcooperative-based learning and Vygotsky'szone of proximal development (ZPD) is presented, along with a description of how these two importantlearning theories may be applied to improvesimulation-based instruction . Findings . When learning new material or skills, learners sometimes need to be assisted with moving through thedisequilibrium process that can occur when the new information contrasts with their existingframes of reference or ways of knowing.Cooperative-based learning and thezone of proximal development (ZPD) can be used to assist the learner with working through thedisequilibrium process, includingaccommodating andassimilating the new skills and information into their ownpractice . Limitations/Implications . Gaps in thesimulation literature, including ways to implement both theories into practice, can lead to incomplete orineffective simulation-based instruction practices. Originality/Value . Many organizations have implementedsimulation into theirpatient safety program, but have not considered how thezone of proximal development (ZPD) andcooperative-based learning can be used to improveeducational outcomes .